Institusionalisasi Demokrasi Deliberatif di Indonesia: Sebuah Pencarian Teoretik - Faishal, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2007)
This paper aim to understanding a tranformation of deliberative democracy installation in Indonesia. The measure of succestfully democratic society based on two tradition, first from liberal society and second, from communitarian society. This paper claim that deliberative categorized are sufficiently in Indonesian politics and have a good modality, This paper explored a local modality called permusyawaratan (deliberated) and perwakilan (representation) and comparison that with universal terms which came from western tradition. The main focus is political system which deliberative democracy making a good home ground. Especially in structural context in Indonesian state body.